![1)2^{x}-2^{x-2}=3\\\\2^{x-2}(2^{2} -1)=3\\\\2^{x-2}*3=3\\\\2^{x-2}=1\\\\2^{x-2}=2^{o}\\\\x-2=0\\\\x=2 1)2^{x}-2^{x-2}=3\\\\2^{x-2}(2^{2} -1)=3\\\\2^{x-2}*3=3\\\\2^{x-2}=1\\\\2^{x-2}=2^{o}\\\\x-2=0\\\\x=2](https://tex.z-dn.net/?f=1%292%5E%7Bx%7D-2%5E%7Bx-2%7D%3D3%5C%5C%5C%5C2%5E%7Bx-2%7D%282%5E%7B2%7D%20-1%29%3D3%5C%5C%5C%5C2%5E%7Bx-2%7D%2A3%3D3%5C%5C%5C%5C2%5E%7Bx-2%7D%3D1%5C%5C%5C%5C2%5E%7Bx-2%7D%3D2%5E%7Bo%7D%5C%5C%5C%5Cx-2%3D0%5C%5C%5C%5Cx%3D2)
0\\\\m^{2}-30m+81=0\\\\m_{1} =3;m_{2}=27\\\\3^{x}=3\\\\x_{1}=1\\\\3^{x}=27\\\\3^{x}=3^{3}\\\\x_{2}=3" alt="2)3^{2x}-30*3^{x}+81=0\\\\3^{x}=m,m>0\\\\m^{2}-30m+81=0\\\\m_{1} =3;m_{2}=27\\\\3^{x}=3\\\\x_{1}=1\\\\3^{x}=27\\\\3^{x}=3^{3}\\\\x_{2}=3" align="absmiddle" class="latex-formula">
![3)5^{x}<625\\\\5^{x}<5^{4}\\\\x<4 3)5^{x}<625\\\\5^{x}<5^{4}\\\\x<4](https://tex.z-dn.net/?f=3%295%5E%7Bx%7D%3C625%5C%5C%5C%5C5%5E%7Bx%7D%3C5%5E%7B4%7D%5C%5C%5C%5Cx%3C4)
x ∈ (- ∞ ; 4)
![4)(\frac{3}{4})^{x-3}\leq(\frac{4}{3})^{2x+5}\\\\(\frac{4}{3})^{3-x} \leq(\frac{4}{3})^{2x+5}\\\\3-x\leq2x+5\\\\-x-2x\leq5-3\\\\-3x\leq2\\\\x\geq-\frac{2}{3} 4)(\frac{3}{4})^{x-3}\leq(\frac{4}{3})^{2x+5}\\\\(\frac{4}{3})^{3-x} \leq(\frac{4}{3})^{2x+5}\\\\3-x\leq2x+5\\\\-x-2x\leq5-3\\\\-3x\leq2\\\\x\geq-\frac{2}{3}](https://tex.z-dn.net/?f=4%29%28%5Cfrac%7B3%7D%7B4%7D%29%5E%7Bx-3%7D%5Cleq%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7B2x%2B5%7D%5C%5C%5C%5C%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7B3-x%7D%20%5Cleq%28%5Cfrac%7B4%7D%7B3%7D%29%5E%7B2x%2B5%7D%5C%5C%5C%5C3-x%5Cleq2x%2B5%5C%5C%5C%5C-x-2x%5Cleq5-3%5C%5C%5C%5C-3x%5Cleq2%5C%5C%5C%5Cx%5Cgeq-%5Cfrac%7B2%7D%7B3%7D)
x ∈ [- 2/3 ; + ∞)
![5)4^{x}+2^{x+1}=80\\\\(2^{x})^{2}+2*2^{x} -80=0\\\\2^{x}=8\\\\2^{x}=2^{3}\\\\x=3\\\\2^{x}=-10<0 5)4^{x}+2^{x+1}=80\\\\(2^{x})^{2}+2*2^{x} -80=0\\\\2^{x}=8\\\\2^{x}=2^{3}\\\\x=3\\\\2^{x}=-10<0](https://tex.z-dn.net/?f=5%294%5E%7Bx%7D%2B2%5E%7Bx%2B1%7D%3D80%5C%5C%5C%5C%282%5E%7Bx%7D%29%5E%7B2%7D%2B2%2A2%5E%7Bx%7D%20-80%3D0%5C%5C%5C%5C2%5E%7Bx%7D%3D8%5C%5C%5C%5C2%5E%7Bx%7D%3D2%5E%7B3%7D%5C%5C%5C%5Cx%3D3%5C%5C%5C%5C2%5E%7Bx%7D%3D-10%3C0)
решений нет
Ответ : 3
![6)log_{\frac{1}{2} }(2x+3)=0 6)log_{\frac{1}{2} }(2x+3)=0](https://tex.z-dn.net/?f=6%29log_%7B%5Cfrac%7B1%7D%7B2%7D%20%7D%282x%2B3%29%3D0)
ОДЗ :
2x + 3 > 0
2x > - 3
x > - 1,5
![2x+3=(\frac{1}{2} )^{o}\\\\2x+3=1\\\\2x= -2\\\\x=-1 2x+3=(\frac{1}{2} )^{o}\\\\2x+3=1\\\\2x= -2\\\\x=-1](https://tex.z-dn.net/?f=2x%2B3%3D%28%5Cfrac%7B1%7D%7B2%7D%20%29%5E%7Bo%7D%5C%5C%5C%5C2x%2B3%3D1%5C%5C%5C%5C2x%3D%20-2%5C%5C%5C%5Cx%3D-1)
Ответ : - 1